Konsep Pendidikan Akhlak dalam Kitab Adabul ‘Alim Wal Muta’alim (Studi Pemikiran Kh. Khasyim Asy-Ari) dan Relevansinya Dengan Pendidikan di Era Digitalisasi - Listianah Listianah; Muhammad Fazlur Rahman Hadi; Rahmat Arofah Hari Cahyadi (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The purpose of this article is to investigate the ideas of KH. Hasyim Asy'ari regarding pesantren education and to explore the aspects of modernity relevant to the current educational context. The significance of this research lies in the contribution of KH. Hasyim Asy'ari to the transformation of the pesantren education system from moral-based character aspects to organizational structure and curriculum. This represents a significant innovation that remains relevant in the current educational context. By referring to various literature and works by KH. Hasyim Asy'ari, this article combines theory with policy implementation at Pesantren Tebuireng, Jombang. The research method used is literature review with a qualitative approach. Data were collected from articles, books, and other documents, then analyzed using philological content analysis, which connects the educational ideas of KH. Hasyim Asy'ari with current developments. The research findings conclude that: 1) The main focus of KH. Hasyim Asy'ari's educational thought is to humanize people by making them aware of their rights and obligations to God as the creator; this forms the basis for character education. 2) Islamic education is not only about religious knowledge but also includes general knowledge. Therefore, integrating general subjects into the pesantren curriculum is crucial. 3) Pesantren must be able to respond to the changing times without sacrificing its traditional values.